2020
DOI: 10.1177/0021998320931906
|View full text |Cite
|
Sign up to set email alerts
|

Physical and mechanical performance of bentonite and barite loaded low density polyethylene composites: Influence of surface silanization of minerals

Abstract: In this study, two kinds of mineral fillers, bentonite (BNT) and barite (BRT), were incorporated into low density polyethylene (LDPE) by extrusion process. Silane treatment was applied to BRT and BNT surfaces in order to increase their compatibility with LDPE matrix. Surface characteristics of fillers were examined by Fourier transformed infrared spectroscopy (FTIR). LDPE-based composites were prepared at a constant concentration of 10%wt for each additives. Test samples were shaped by injection molding proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 56 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…Si‐related peaks gave higher intensities for Si‐FLS compared to neat FLS thanks to the formation of a silane layer on the mineral surface. [ 25,26,33,34 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Si‐related peaks gave higher intensities for Si‐FLS compared to neat FLS thanks to the formation of a silane layer on the mineral surface. [ 25,26,33,34 ]…”
Section: Resultsmentioning
confidence: 99%
“…FLS and QRZ minerals were subjected to a silane modification process according to similar routes in the literature. [25,26] Silane treatment to FLS and QRZ minerals was applied by mixing powders in a 2 wt% APTES/ethanol solution at pH of 5.0 for nearly 150 min at room temperature and dried at a laboratory owen at 80 C overnight. Silanemodified FLS and QRZ samples were coded as Si-FLS and Si-QRZ, respectively.…”
Section: Surface Silanization Of Mineralsmentioning
confidence: 99%
See 1 more Smart Citation
“…An example of such a mineral is bentonite-a naturally occurring clay mineral with very small particle sizes and a high degree of plasticity [22]. Studies showed that the introduction of an additive to the polymer matrix has a positive effect on the thermal and mechanical properties of the composite, such as hardness, tensile strength and elongation [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, bentonite has a high sorbent property, expansion capacity, and high elastic modulus. Therefore, the incorporation of low levels of BNT in polymeric matrices can induce a decrease in water vapor permeability and increase the thermal, gas barrier and mechanical properties, which are desirable for application in packaging, the purpose of the present study 12,14 …”
Section: Introductionmentioning
confidence: 99%